(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 1990)
On the base of some tentative geological profiles across the external areas of the Lucanian Apennines (Southern Italy), worked out by means of field and well data, has been possible to restare the generai geometrical framework. The results allow to discuss the possible evolution in time and space of the processes associated with the thrust faulting. Starting from the external zones it’s possible to recognize two major structural elements: the Apulian Foreland and the Apenninic Chain. The Apulian Foreland, a very thick from Mesozoic to Pleistocene carbonate sequence, is downfaulted toward SW giving rise to a foredeep: the Bradanic Trough. Internal to this foredeep zone a carbonate platform more or less deformed from Upper Miocene onwards, has been recognized. It probably represents the more internal extension of the Apulian platform. Thus we distinguish an "Apulian Chain" representing a sector of the foreland, deformed since Late Miocene times, from the Apulian Foreland, where extensional regime was predominant.